Various protocols of extracorporeal shock wave therapy in the treatment of stable angina - M. M. Shcherbak; E. L. Shkolnik; Yu. A. Vasyuk; E. N. Yushchuk; E. Yu. Trush; G. Burneykaite; E. Chelutkene; G. Yakutis; G. Zuoziene; B. Petrauskiene (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To evaluate effects of various protocols of cardiac shock wave therapy (CSWT) on quality of life and exercise tolerance in patients with stable angina against the background of optimal medication therapy (OMT).Material and methods. Overall 53 patients (37 men, 16 women) were included in the study. The mean age of examined patients was 67,3±8,1 years. Inclusion criteria: CCS class I-IV angina pectoris, stable therapy for at least 1 month before inclusion in the study and a stable course of coronary artery disease for more than 3 months (no cardiovascular events) before inclusion in the study. Patients were divided into 2 groups. The Group 1 (n=37) received OMT+CSWT standard-modified protocol, Group 2 (n=16) received OMT+CSWT rapid-modified protocol. Electrocardiography, echocardiography, treadmill test, and Seattle quality of life questionnaire (SAQ) were performed at inclusion and 6 months follow up.Results. Both CSWT with rapid-modified protocol and standard-modified protocol significantly reduced the number of short-acting nitrates from 2 (2; 7) to 1 (0; 2) (p=0,04) and from 2 (0; 6) to 0 (0; 2) (p ≤0,001) at 6 months, respectively, as well as the number of angina attacks per week (from 4 (2; 7) to 1 (1; 1) (p=0,007) and 6 (2; 20) to 1 (0; 5) (p ≤0,001). Treadmill test total exercise duration was significantly increased from 393 (326; 574) to 561 (411; 650) seconds (p=0,007) and 365+140,4 to 411,5±156,1 seconds (p=0,01), respectively. Time to 1 mm ST segment depression was also significantly increased from 399,8+169 to 460+182 seconds (p ≤0,05) and from 303,1+179 to 389,9+203 seconds (p=0,001), respectively.Conclusion. In our study, CSWT with rapid-modified protocol improved quality of life and exercise tolerance in patients with stable angina similar to the standard-modified protocol. Rapid-modified protocol of CSWT reduced total duration of the treatment.